SUBJECTIVE REFLECTION IN THE NOVEL OF M. LERMONTOV «HERO OF OUR TIME» AS A MEANS OF EXPRESSING THE POETISATION OF PROSE - A. S. Gladkova (Гуманитарные и юридические исследования)
The article is devoted to the analysis of subjective reflection in the novel of M. Lermontov «Hero of our time» from the standpoint of the creation of the phenomenon of poetic prose. The topic touches the problem of identity, kinship and genre structure of Lermontov's novel.